Empowering local communities: decentralization, empowerment and community driven development - Ahmad, Muhammad Shakil (Springer, 2015)
The Governance and development practitioners discourse continues to embrace community participation and community empowerment as an elementary means of building local capacity towards improving quality of life, poverty reduction, development and change at local level. This article illustrates a review of decentralization initiative of local government system after announcement of devolution plan in Pakistan and appraises its participatory methods to ascertain how far they have improved the process of community development at local level. This article also measure the impact of community empowerment on the sustainability of community driven projects implemented under decentralization initiatives through community based organizations called Citizen Community Board's (CCB's). The results acknowledge the human development and improvement in community empowerment and sustainability of projects at local but yet sense of community and shared benefits to be translated for rural communities. The fundamental goal of decentralization seems to be elusive as only power was transferred at local level, whereby there is less support for community capacity building, community access to resources, still there is elite holding over the electoral process. It is argued that community development initiatives in Pakistan require continues support from local government to boost local rural economies. Likewise, community-local government participatory development strategies can attain strong local ownership and empowerment among rural communities.